THE ROLE OF SMALL AND MEDIUM-SIZED ENTERPRISES (SMEs) IN REGIONAL DEVELOPMENT AND PROGRESS OF CONVERGENCE IN BULGARIA - Michaela Georgieva (Journal of Bio-Based Marketing)
The following article is dedicated to an examination of the issues currently facing small and medium-sized enterprises (SMEs) and the challenges they have faced in recent years. The authors contend that SMEs in Bulgaria have the potential to serve as the cornerstone of regional development, thereby facilitating the enhancement of the economic situation in all regions of the country. It is crucial to acknowledge that the advancement of small and medium-sized enterprises necessitates an in-depth examination of the challenges and obstacles they confront in establishing themselves within specific regions. Such an approach will also demonstrate the processes of regionalization and facilitate the promotion of social development in regions such as the North East, where SMEs require further assistance. After the article, the authors have proposed pertinent conclusions and made recommendations that they believe can assist the process of regional development and convergence of Bulgarian business within the European Union.